2007
DOI: 10.3998/ark.5550190.0008.g03
|View full text |Cite
|
Sign up to set email alerts
|

Combined drug design of potential Mycobacterium tuberculosis and HIV-1 inhibitors: 3’,4’-di-substituted -4'H-spiro[isothiochromene-3,5'-isoxazol]-4(1H)-one

Abstract: We report herein the design and synthesis of 17 new spiroheterocycles 10-26, on the basis of two hypothetical pharmacophore structures designed to interact with both of Mycobacterium tuberculosis bacteria and HIV-1 virus. The in vitro biological evaluation of these compounds allowed us to point out seven new potential non-nucleoside hits, with MIC values in the range of 6.25 µg/mL and two new potential anti-HIV-1 inhibitors .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It was believed that amide can exist in two major tautomeric forms, keto-amine and hydroxy-enamine, although keto-amine form is predominant in the solid state [ 28 ] as shown in Figure 1 . We investigated the potential pharmacophores of various bioactive compounds for their antibacterial [ 29 33 ], antifungal [ 34 , 35 ] and antiviral activity [ 36 ], and verified them further with Petra/Osiris/Molinspiration (POM) analyses. On the basis of our previously published findings in antibacterial, antiviral and antifungal fields, we can safely conclude that our present series, ABD 1 – 10 , also contain a pharmacophore responsible for antifungal and antibacterial activities which is elaborated in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It was believed that amide can exist in two major tautomeric forms, keto-amine and hydroxy-enamine, although keto-amine form is predominant in the solid state [ 28 ] as shown in Figure 1 . We investigated the potential pharmacophores of various bioactive compounds for their antibacterial [ 29 33 ], antifungal [ 34 , 35 ] and antiviral activity [ 36 ], and verified them further with Petra/Osiris/Molinspiration (POM) analyses. On the basis of our previously published findings in antibacterial, antiviral and antifungal fields, we can safely conclude that our present series, ABD 1 – 10 , also contain a pharmacophore responsible for antifungal and antibacterial activities which is elaborated in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Tautomerism in bioactive compounds plays a key role in the orientation of bioactivity of drugs that have found wide application in drug design, ranging from new medicinal materials to antibacterial imidazo[1,2-a]pyrimidine (-pyridine), 46 as sulphonamides in the antifungal agents 47 and as potential antiHIV spiroheterocycles. 48 Similar to HPMBP, compound 6 is also likely to exist as four tautomers (Scheme 3) in water, although it exists as tautomer 6c in the solid state. To understand the inhibitory mechanism and acting sites of compound 6 to 20S proteasome, knowing which tautomer actually exists in the solution environment is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable theoretical concept is that proposed by Ben Hadda et al [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] apropos of definition of pharmacophore site. The best descriptors for studying and identifying the type of pharmacophore site (antibacterial, antiviral or antitumor) are the description in detail of local electrophilicity and the nucleophilicity of each functionalized group and their spatial arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Recently, it has been shown that the kinase inhibition by an organometallic systems under biological condition may be significantly facilitated if a ligand containing an anti-kinase pharmacophore (NH-C=O), a bidentate N,N coordinative site (staurosporine derivatives) and non-toxic metal (ruthenium) are available. [2][3][4][5][6] The cancer inhibition of kinase enzymes through organic drugs has been the subject of different theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation